The Conducive Learning Environment and its Role in Improving the Quality of teacher-student Relationships during physical education lessons - Soran, Entethar (Indonesian Journal of Sport Management, 2025)
Conducting studies on the conducive learning environment and its role in improving the teacher-student relationship quality during physical education lessons is important because it catalyzes transformational change within the sports education scene. Therefore, this research aims to identify the suitability of the physical education teaching environment within the preparatory schools affiliated with the Nineveh Education Directorate (center). Also, it seeks to determine the level of quality in the relationships between physical education teachers and students. In this research, the researcher adopted the descriptive approach using the survey and correlation methods. The researcher identified the research population as physical education teachers in preparatory schools affiliated with the Nineveh Education Directorate (center) for the academic year (2024-2025), whose number is 469 physical education teachers. The researcher randomly selected (212) teachers based on the sample size calculation. After applying the tools, extracting the results, and processing them statistically, the researcher reached several conclusions: the learning environments in physical education lessons within the preparatory schools affiliated with the Nineveh Education Directorate (center) are characterized by being of a low level in terms of their suitability for the educational process from the point of view of physical education teachers there. They also found the physical education teachers in the preparatory schools affiliated with the Nineveh Education Directorate (center) enjoy a low-quality relationship with their students within the lessons from their point of view. The researcher recommended that the responsible educational authorities in the directorates of education and their various departments use the two tools developed to assess the levels of conducive learning environments for different academic subjects and examine the quality of relationships between teachers of multiple subjects and their students.